Fetal and neonatal outcome in severe alloimmunization managed with intrauterine transfusion: 18-year experience in a tertiary referral hospital in China - Pan, Wenxu; Wu, Haiyan; Chen, Junlin; Mo, Xinyue; Wang, Hongxin; Fang, Qun; Li, Yijuan; Huang, Yuefang (Frontiers in Pediatrics, 2023)
Background: Hemolytic disease of the fetus and newborn (HDFN) due to red cell alloimmunization, is an important cause of fetal and neonatal morbidity and mortality. However, fetal and neonatal outcome of HDFN managed with intrauterine transfusion (IUT) in China are unknown. In addition, fetal and neonatal outcomes according to the type of maternal red cell alloantibodies involved and outcomes of hydrops fetalis are also unclear. Objectives: The objective of this study was to evaluate fetal and neonatal outcomes of severe red-cell alloimmunization treated by IUT, to compare the outcomes according to the type of antibody, and to investigate the perinatal and postnatal outcomes of hydrops fetalis due to red cell alloimmunization. Methods: A retrospective study of pregnancies affected by HDFN and managed with IUT at a tertiary care university hospital in China between January 2001 and December 2018 was performed. Fetal and neonatal outcomes were investigated, and comparison of outcomes depending on the type of antibody and comparison of outcome between hydrops fetalis and fetuses without hydrops were also conducted. Results: 244 IUTs were performed in 81 fetuses from 80 pregnancies. Anti-RhD was the major etiology of HDFN requiring IUT (71.6%). The fetal survival rate was 90.1%. The survival rate of the hydropic fetuses was significantly lower than those of the non hydropic fetuses (61.2% versus 95.6%) (p=0.002**). Compared with non hydropic fetuses, hydropic fetuses had significantly lower gestational age and lower hemoglobin level at first IUT. The neonatal survival rate was 98.6%. Exchange transfusions were required in 26% of the neonates. 30.1% of neonates had late anemia and required top-up transfusions, and hydropic fetuses required more late top-up transfusions than fetuses without hydrops. No significant difference in fetal and neonatal outcomes was found among the four subgroups stratified by the antibody involved. Conclusion: Our study demonstrates that IUT is an effective and safe therapy for severe HDFN at our institution. Early detection and treatment of hydrops is critical for perinatal outcomes. Particular attention should be paid to late postnatal anemia in affected neonates and top-up transfusion is still commonly needed.